Definition of international competences: experience of the history department at universidad nacional de colombia in the alfa tuning latin america – europe project - Campos Rodríguez, Darío (Universidad Pedagógica y Tecnológica de Colombia, 2011)
This research paper describes the political and social conditions that surround the emergence of the Tuning project in Europe, its scope, perspectives and actions with regard to the consensus in higher education mediated by the Bologna Declaration, as well as its appropriation for Latin American practices and their effects. This study uses history as a case study, analyzing the set of skills that the Tuning project promotes, and the various forms that have been installed, through statistical studies in various programs and faculties, in Latin American and Colombian universities. The article intends to raise a critique of the concept of curricular convergence proposed and implemented by this project.